The role of contamination history and gender on the genotoxic responses of the crayfish Procambarus clarkii to a penoxsulam-based herbicide - Costa, Ricardo (Ecotoxicology (London, England), 2018)
The responses of non-target organisms to pesticide exposure are still poorly explored in what concerns the development of adjustments favouring population success. Owing to the vital role of DNA integrity, it is important to identify genome-maintenance skills and their determinant factors. Thus, the major aims of the present study were: (i) to assess the genotoxicity of the penoxsulam-based herbicide (Viper®) to the crayfish Procambarus clarkii; (ii) to understand the influence of gender and contamination history in the genotoxic responses following exposure to this herbicide; (iii) to investigate the damage mechanisms involved in putative adjustments shown by P. clarkii. Two populations were tested, one from a reference site and the other from a historically contaminated site. Specimens from both populations were exposed to Viper®, considering environmentally relevant penoxsulam concentrations (20 and 40 µg L-1) and to a model genotoxicant (EMS). Comet assay was adopted to assess the genetic damage in gills. The results disclosed the genotoxicity of the herbicide to crayfish (a non-target organism). Additionally, organisms exposed to the highest concentration of penoxsulam signalized the influence of factor "population" towards the genotoxic pressure (measured as effective DNA breaks): P2 males from the historically impacted population displayed a significantly higher susceptibly (by up to 53.98%) when compared to control, while the homologous group from the reference population presented levels similar to its respective control. When DNA lesion-repair enzymes were considered, DNA oxidation patterns suggested an increased ability of this gender (39.75% lower than negative control) to deal with this particular type of damage, namely considering pyrimidines oxidation. It is worth remarking that the influence of the exposure history on the protection/vulnerability to the penoxsulam-based herbicide was only evident in males, despite depending on the type of DNA damage: when the non-specific damage was considered, organisms from the impacted population seemed to be more vulnerable while regarding to the oxidative damage, males from the impacted population appeared to be more protected than organisms that have never been exposed to penoxsulam. Overall, the influence of factors "gender" and "contamination history" was demonstrated as well as its dependence on DNA damage type was evident. EMS groups did not present the differences between populations, reinforcing the agent-specific adjustment hypothesis.These findings highlighted the importance of considering differential physiological backgrounds in ecogenotoxicological analysis, hence favouring the elaboration of more plausible and holistic approaches integrating the environmental risk assessment of pesticides